2023
DOI: 10.3389/fpls.2023.1124046
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-scale genomics, metabolomics, and transcriptomics provide insight into the synthesis and regulation of phenols in Vitis adenoclada grapes

Abstract: Vitis adenoclada is a wild grape unique to China. It exhibits well resistance to heat, humidity, fungal disease, drought, and soil infertility. Here, we report the high-quality, chromosome-level genome assembly of GH6 (V. adenoclada). The 498.27 Mb genome contained 221.78 Mb of transposable elements, 28,660 protein-coding genes, and 481.44 Mb of sequences associated with 19 chromosomes. GH6 shares a common ancestor with PN40024 (Vitis vinifera) from approximately 4.26–9.01 million years ago, whose divergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…This led to differences in the expression of phenolic constituents. Phenolics serve as substrates in the enzymatic browning process (Wang et al., 2023c). The types and concentrations of phenolics exhibit significant variation across different organisms, leading to differences in the specific phenolics that play a major role in the browning process (Wang et al., 2023c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to differences in the expression of phenolic constituents. Phenolics serve as substrates in the enzymatic browning process (Wang et al., 2023c). The types and concentrations of phenolics exhibit significant variation across different organisms, leading to differences in the specific phenolics that play a major role in the browning process (Wang et al., 2023c).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Wang et al. (2023c) employed integrated metabolomics to identify the browning substrates of apples, which encompass anthocyanins, tannins, erucic acid, and catechuic acid as their catalytic substrates. The study's findings demonstrated that within phenylpropanoid biosynthesis, phenolics such as chlorogenic acid and ferulic acid exhibit significant downregulation during the browning process of the scraped ginger.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Studies on these genomes focused on grape berry quality (sugar, acid, aroma, pigment, and so on) [ 7 , 12 , 18 ], biotic and abiotic resistance [ 2 , 13 ], and future breeding strategies [ 9 , 22 ]. Through these genomes, researchers explored the mechanisms of disease resistance, high tannin content, and new breeding strategies.…”
Section: Grape Genomics Provide the Basis Of Grape Studiesmentioning
confidence: 99%
“…Wild grape, which has high genetic diversity, has also been an important subject of grape genomic studies [ 10 , 13 , 18 ]. Wild Vitis species are widely found in the north of temperate zones and subtropics.…”
Section: Grape Genomics Provide the Basis Of Grape Studiesmentioning
confidence: 99%
See 1 more Smart Citation